PHYSICOCHEMICAL AND MICROBIAL ANALYSIS OF MINIMALLY PROCESSED FRUITS AND VEGETABLES - M. PENCHALARAJU, K. SOWJANYA, K. MANJULA V.S. PRASAD MASANAM and (The Journal of Research, PJTSAU, 2017)
Minimal processing foods gives additional value to fresh cuts in terms of convenience and time saving, although several hurdles are encountered due to the difficulty in preserving their freshness for prolonged periods. These products in fact are characterized by their shorter life than their whole counter parts because of microbial spoilage, increased respiration rate, etc. Hence, the present study was carried out to know the physico-chemical parameters (PH, moisture, acidity)and microbial analysis (TPC and yeasts and moulds) of minimally processed fruits and vegetables at different storage periods i.e. at 0, 3rd, 5th day respectively. Consumer Survey was carried out to know the maximum consumption and the most frequently consumed fruits and vegetables in local areas of Hyderabad and it was observed that the consumption of sprouted seeds and individually processed cabbage and cauliflowers was high.Among the physicochemical parameters, the moisture content of minimally processed pineapple and cabbage decreased during different storage periods. pH and acidity decreased during different storage periods. The microbial parameters i.e., TPC and yeasts / moulds content increased both for pineapple and cabbage during different storage periods.